Minimum quality standards and predatory behaviour - Luca Lambertini; Carlo Scarpa (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper shows that the introduction of a minimum quality standard can have repercussions on market structure, opening the possibility of predatory behaviour. The predatory equilibrium exists independently of whether or not adjustment costs are present. Moreover, whenever predation is an equilibrium, it is selected by the risk dominance criterion.
Keywords: L12; L13; 330; MQS; vertical differentiation; predatory behaviour; Produktqualität; Standardisierung; Verdrängungswettbewerb; Duopol; Anpassungskosten; Theorie